Pelastusdokumentointi tehtaissa - Kupila, Sanna (Tekniikan Waiheita, 2012)
Salvaging factories through documentation Contemporary documentation in a wide sense has been a part of the Turku Museum Centre from the early 2000s, when the museum documented the Tunturi bicycle factory. This documentation provides information about various production processes for the museum archive. Factory work processes are preserved through words and images. The factory workers participate in the documentation through their roles within the factory, but their working lives have not been preserved as a whole. When production at the candy factory Leaf Oy was run down in Turku in 2005–2007, the Turku Museum Centre was given sole access to document the factory’s production processes. The cultural value of the old factory buildings was also determined at the same time, to guide future re-use. The Museum Centre has also documented processes on cruise ships between Turku and Stockholm and baking companies in Turku. Industrial documentation by museums is important because companies do not always document their current processes. The present day is often too close for us to realise its value. This is why researchers are needed in factories to point out that tomorrow, today is yesterday and that the present day will soon be history.